The Effectiveness of Relaxation Techniques in Reducing Parenting Stress in Generation Z Mothers - Aulia, Fitri; Zain, Maulidiana; Muhlis; Ernawati; Wulanjati, Syara (Al Huwiyah: Journal of Woman and Children Studies, 2025)
This study aims to analyze the effectiveness of relaxation techniques in reducing parenting stress among Generation Z mothers at Hamzanwadi Early Childhood School. The research design used was quantitative with a pre-experimental one group pretest–posttest approach. The study subjects involved 50 Gen Z mothers who have children attending Hamzanwadi Kindergarten. This study applied a total sampling (census) technique, whereby the entire population was included as the research sample. Parenting stress was measured using a Likert-scale questionnaire instrument that has been tested for validity and reliability. The research intervention was the provision of relaxation techniques adapted from the breathing relaxation and progressive muscle relaxation approach, which was implemented in a structured manner over four sessions. The results of descriptive statistical analysis showed a significant decrease in parenting stress levels after the relaxation intervention. The average stress score in the pretest was 76.62 (SD = 6.46), while the average stress score in the posttest was 61.20 (SD = 7.38), with a decrease in the average stress score reaching 15.42 points. These findings indicate that relaxation techniques are effective in reducing parenting stress among Gen Z mothers in the early childhood school environment. The results of this study reinforce the urgency of implementing relaxation techniques as a well-being-based counseling intervention strategy for caregivers in childcare institutions and contribute to the development of parent mental health support services at the early childhood education level in local communities.